Climatic consequences of the process of saturation of radiation absorption in gases - Jan Kubicki; Krzysztof Kopczyński; Jarosław Młyńczak (Applications in Engineering Science, 2024)
This article provides a brief review of research on the impact of anthropogenic increase in atmospheric CO2 concentration on Earth's climate. A simplified analysis of resonant radiation absorption in gases is conducted. Building upon the material from the cited articles, theoretical and empirical relationships between radiation absorption and the mass of the absorbing material are presented. The concept of saturation mass is introduced. Special attention is given to the phenomenon of thermal radiation absorption saturation in carbon dioxide. By comparing the saturation mass of CO2 with the quantity of this gas in Earth's atmosphere, and analyzing the results of experiments and measurements, the need for continued and improved experimental work is suggested to ascertain whether additionally emitted carbon dioxide into the atmosphere is indeed a greenhouse gas. Significance statement: • The impact of anthropogenic increase in atmospheric CO2 concentration on Earth's climate is analysed. • The concept of saturation mass is introduced. • By comparing the saturation mass of CO2 with the quantity of this gas in Earth's atmosphere, and analyzing the results of experiments and measurements, the need for continued and improved experimental work is suggested to ascertain whether additionally emitted carbon dioxide into the atmosphere is indeed a greenhouse gas.